MUCOLYTIC THERAPY IN INFANTS - I. V. Davydova; T. V. Turti; V. V. Altunin (Педиатрическая фармакология, 2013)
When prescribing mucolytic therapy for bronchopulmonary diseases to infants, it is necessary to consider not only peculiarities of a small child’s respiratory tract, but also action of mucolytic drugs. The authors exemplify their data on efficacy and safety of the use of mucolytics in children under 2 years of age with acetylcysteine.